A rare case of laparoscopic repair of incarcerated femoral hernia in patient of rheumatic heart disease with double valve replacement - Ambekar, Sachin; Shankar, Mrinal (International Surgery Journal, 2018)
Femoral hernias are very rare presentation in comparison to inguinal hernia. Femoral hernias are a protrusion of the peritoneal sac covered with an extraperitoneal pad of fat through the femoral canal. Mostly an acquired condition often with incarceration or strangulation. Laparoscopic repair of femoral hernia has a learning curve for surgeons and now being preferred by majority surgeons to the conventional open repair. We report a case of a 65 year female as a high risk case of rheumatic heart disease who had underwent double valve replacement in recent, was undertaken for total laparoscopic extraperitoneal repair with meshplasty for the incarcerated femoral hernia on left side, with faster recovery of patient postoperatively. Laparoscopic repair of a femoral hernia reduces the risk of reoperation for a recurrence compared with open repair.